Media and journalism professionals a practical career guide - Hamilton, Tracy Brown (Lanham, Maryland Rowman & Littlefield, an imprint of The Rowman & Littlefield Publishing Group, Inc., 2021)
"Media and Journalism Professionals: A Practical Career Guide includes interviews with professionals in a field that has proven to be a stable, lucrative, and growing profession"-- Provided by publisher.
Why choose a career in media and journalism? -- Forming a career plan -- Pursuing the education path -- Writing your resume and interviewing.
Includes bibliographical references.
Keywords: Mass media -- Vocational guidance; Journalism -- Vocational guidance